Pelatihan untuk Meningkatkan Efektivitas dan Akuntabilitas Pelaporan Keuangan Koperasi - Reny Aziatul Pebriani; Tien Yustini; Rafika Sari; Nur Kholis (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
This service aims to increase the effectiveness and accountability in cooperative financial reporting through the implementation of training. The main focus of this training is to provide cooperative members with an in-depth understanding of the required financial reporting information and how to compile it accurately by utilizing the application created using the simple application in Ms. Excle. The community service method is carried out in the form of training starting from a group discussion forum, partner situation analysis, pretest, main training activities and post test. The results of this community service activity show that there is an increase in the knowledge, skills and abilities of partners in understanding the effectiveness and accountability in the financial management of the Cooperative by utilizing the application used. With this increased understanding, it is hoped that cooperatives can be more effective in presenting their financial information, supporting appropriate decision-making, and increasing trust from related parties.